Banking Services and Investments in Cameroon: An Approach by the ARDL Method - Robert, Tangakou Soh; Arsène, Mba Fokwa (Asian Journal of Economic Modelling, 2015)
This article intends to determine the effects of banking on private investment in Cameroon. Using data from the World Bank for the period 1980-2012, the ARDL (Auto Regressive Distributed Lag Model) method allowed us to determine the cointegration’s relationships between the different variables and the optimal number of delays associated with each variable. After estimating the Vector Error Correction Model (VECM), it has produced the following results: private investments in Cameroon are positively and significantly influenced by the government spending, the growth rate, and the devaluation. However, the rate of banking, bank credits and inflation rate have a significant negative impact on investments. If there is a real reduction of uncertainty by government authorities, banks will be able to play their true role of financial intermediary and the financing aspect of investments will be more effective and productive.